2016
DOI: 10.1186/s12870-016-0866-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome sequencing and de novo analysis of Vaccinium corymbosum during fruit and color development

Abstract: BackgroundBlueberry is an economically important fruit crop in Ericaceae family. The substantial quantities of flavonoids in blueberry have been implicated in a broad range of health benefits. However, the information regarding fruit development and flavonoid metabolites based on the transcriptome level is still limited. In the present study, the transcriptome and gene expression profiling over berry development, especially during color development were initiated.ResultsA total of approximately 13.67 Gbp of da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 23 publications
0
30
1
Order By: Relevance
“…As demonstrated by cluster analysis (Supplementary Figure S3), glycosylation and acylation, two enzymatic reactions that contribute to anthocyanin diversification in plants (Jaakola et al, 2002;Noguchi et al, 2009;Zifkin et al, 2012;Cheng et al, 2014;Le Roy et al, 2016) can explain the diversity observed within the tetraploid accessions. Previous studies described genes involved in flavonoid and more specifically anthocyanin biosynthesis in blueberry (Jaakola et al, 2002;Kurilich et al, 2005;Charron et al, 2009;Zifkin et al, 2012;Jaakola, 2013;Li et al, 2016;Lin et al, 2018;Colle et al, 2019). Here based on data from multiple studies (Jaakola et al, 2002;Zifkin et al, 2012;Jaakola, 2013;Colle et al, 2019), we reconstructed a scheme of the flavonoid pathway in blueberry (Figure 9) that includes early and late biosynthetic genes (EBGs and LBGs, respectively).…”
Section: Genotypic Effects Explain the Extensive Metabolite And Fruitmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated by cluster analysis (Supplementary Figure S3), glycosylation and acylation, two enzymatic reactions that contribute to anthocyanin diversification in plants (Jaakola et al, 2002;Noguchi et al, 2009;Zifkin et al, 2012;Cheng et al, 2014;Le Roy et al, 2016) can explain the diversity observed within the tetraploid accessions. Previous studies described genes involved in flavonoid and more specifically anthocyanin biosynthesis in blueberry (Jaakola et al, 2002;Kurilich et al, 2005;Charron et al, 2009;Zifkin et al, 2012;Jaakola, 2013;Li et al, 2016;Lin et al, 2018;Colle et al, 2019). Here based on data from multiple studies (Jaakola et al, 2002;Zifkin et al, 2012;Jaakola, 2013;Colle et al, 2019), we reconstructed a scheme of the flavonoid pathway in blueberry (Figure 9) that includes early and late biosynthetic genes (EBGs and LBGs, respectively).…”
Section: Genotypic Effects Explain the Extensive Metabolite And Fruitmentioning
confidence: 99%
“…Here based on data from multiple studies (Jaakola et al, 2002;Zifkin et al, 2012;Jaakola, 2013;Colle et al, 2019), we reconstructed a scheme of the flavonoid pathway in blueberry (Figure 9) that includes early and late biosynthetic genes (EBGs and LBGs, respectively). The early anthocyanin genes (EBGs) are highly conserved across the plant kingdom including Vaccinium species (Jaakola et al, 2002;Zifkin et al, 2012;Jaakola, 2013;Li et al, 2016;Lin et al, 2018;Colle et al, 2019). However, the late anthocyanins biosynthesis genes (LBGs) have not fully explored in Vaccinium.…”
Section: Genotypic Effects Explain the Extensive Metabolite And Fruitmentioning
confidence: 99%
“…Using the MISA software (http://pgrc.ipk-gatersleben.de/misa/misa.html), 145,640 scaffolds of Acer truncatum were used for genomic SSR marker detection. The following search parameters were set for identification: Di-, Tri-, Tetra-, Penta-and Hexa-nucleotide motifs with a minimum of 6, 5, 4, 4 and 4 repeats, respectively, as previously described [29,30]. The primers for SSR markers were designed by Premier 5.0 (Premier Biosoft International, Palo Alto, CA, USA).…”
Section: The Genomic Ssr Markers Detectionmentioning
confidence: 99%
“…The quality of the library was assessed by the Agilent Bioanalyzer 2100 system. The fragments (300 bp ± 25 bp) were purified and amplified as previously reported in detail [5], and then the library was sequenced using the Illumina HiSeq platform.…”
Section: Library Construction For Illumina Sequencing Data Analysis mentioning
confidence: 99%
“…Recent studies have shown that RNA-Seq is a very effective and powerful technique for gathering extensive transcriptome information in many plants [5][6][7][8]. When compared with other hardwood species [9][10][11][12][13][14][15], conifers tend to have larger and highly repetitive genomes [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%